Clinical Features of Acute Flaccid Myelitis Temporally Associated With an Enterovirus D68 Outbreak: Results of a Nationwide Survey of Acute Flaccid Paralysis in Japan, August–December 2015. (6th October 2017) - Chong, Pin Fee; Kira, Ryutaro; Mori, Harushi; Okumura, Akihisa; Torisu, Hiroyuki; Yasumoto, Sawa; Shimizu, Hiroyuki; Fujimoto, Tsuguto; Hanaoka, Nozomu; Kusunoki, Susumu; Takahashi, Toshiyuki; Oishi, Kazunori; et al.
Abstract : Fifty-nine acute flaccid myelitis cases were reported nationwide, coincident with enterovirus D68 (EV-D68) outbreak from August to December 2015. Strong temporal association was noted, and EV-D68 was detected from some cerebrospinal fluid and blood specimens. Antiganglioside antibodies were identified in some patients, and prognostic factors were analyzed. Abstract: Background: Acute flaccid myelitis (AFM) is an acute flaccid paralysis syndrome with spinal motor neuron involvement of unknown etiology. We investigated the characteristics and prognostic factors of AFM clusters coincident with an enterovirus D68 (EV-D68) outbreak in Japan during autumn 2015. Methods: An AFM case series study was conducted following a nationwide survey from August to December 2015. Radiographic and neurophysiologic data were subjected to centralized review, and virology studies were conducted for available specimens. Results: Fifty-nine AFM cases (58 definite, 1 probable) were identified, including 55 children and 4 adults (median age, 4.4 years). The AFM epidemic curve showed strong temporal correlation with EV-D68 detection from pathogen surveillance, but not with other pathogens. EV-D68 was detected in 9 patients: 5 in nasopharyngeal, 2 in stool, 1 in cerebrospinal fluid (adult case), and 1 in tracheal aspiration, nasopharyngeal, and serum samples (a pediatric case with preceding steroid usage). Cases exhibited heterogeneous paralysis patterns from 1- to 4-limb involvement, but all definite cases had longitudinal spinal gray matter lesions on magnetic resonance imaging (median, 20 spinal segments). Cerebrospinal fluid pleocytosis was observed in 50 of 59 cases (85%), and 8 of 29 (28%) were positive for antiganglioside antibodies, as frequently observed in Guillain-Barré syndrome. Fifty-two patients showed variable residual weakness at follow-up. Good prognostic factors included a pretreatment manual muscle strength test unit score >3, normal F-wave persistence, and EV-D68–negative status. Conclusions: EV-D68 may be one of the causative agents for AFM, while host susceptibility factors such as immune response could contribute to AFM development.